(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Mental health is essentially as important as the physical health required of an individual to maintain. There are many factors that seem to play a role in the genesis of mental illness. Objective: This study was conducted among the mentally ill patients admitted to four hospitals of Dhaka city with a view to find out their socio demographic characteristics of mental illness. Materials and Methods: It was a descriptive type of cross sectional study. A total number of 81 patients and their near relatives were interviewed at four medical institutions through a structured questionnaire. A checklist was used for clinical diagnosis of the patients. A master sheet was prepared followed by questionnaire plotting all the information. Then data were analyzed according to objectives and necessary tables were prepared accordingly by case appropriate variables of the study using Microsoft office program. Results: The study results showed that 81.49% patients were male and 18.51% patients were female. Of the total patients 71.61% were found in the age group of unto 30 years. Maximum patients (61.73%) were found within the monthly family income of BDT 2500/- to 4500/- only. 53.03% of patients were married followed by 39.51% of unmarried. The study revealed that 58.02% patients hailed from urban area. 61.73% patients were educated up to secondary level and only 8.64% patients were illiterate. Regarding occupation 27.17% patients were cultivator and 16.05% were students. The study reflected that 48.15% patients were smokers and very few (6.17%) were drug drug addicts. 61.73% patients were living in joint families.50.62% patients did not receive treatment prior to admission. Of the total 49.38% treated cases (prior to admission), 25% cases were treated from the homeopath and only 25% were consulted with specialist. Conclusion: The lower and middle socio economic group and literate group from urban areas living in joint family suffered more from mental illness. There is need for appropriate policy to address the problems of families with mentally ill patients at the family and community levels. Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014